The Registration of Proprietary Land as a Result of Exchange for Village Cash Land Through a Complete Systematic Land Registration Program - Ariyana, Ade Riusma (International Journal of Law Society Services, 2024)
Complete Systematic Land Registration (PTSL) is a land registration process for the first time, which is carried out simultaneously and includes all land registration objects that have not been registered in a village or sub-district area or other names at the same level. Land is not always located in strategic areas. There are several processes including land exchange.The aim of this research is to determine and analyze the process of registration of land ownership resulting from an exchange with village cash land through the PTSL program until the issuance of the certificate of ownership in Cilacap Regency; To find out and analyze what obstacles and solutions are faced by the Applicant, the Cilacap Regency Regional Government, and the Cilacap Regency Land Office in the Process of Registration of Ownership Land as a result of the Exchange with Village Treasury Land through PTSL until the issuance of the Ownership Certificate in Cilacap Regency.This research uses a sociological juridical type of research, the research specifications are descriptive, the data sources used by the author are primary data and secondary data. The results of this research areThe process of exchanging community land for village treasury land in Cilacap Regency is in accordance with applicable regulations, namely in accordance with the Cilacap Regent's Letter dated 22 December 2004 Number: 143/033/00. Meanwhile, the process of registering freehold land resulting from an exchange with village treasury land through the PTSL program in Cilacap Regency is in accordance with PTSL technical instructions Number 1/Juknis-100.Hk.02.01/I/2021 and has been completed until the issuance of the Ownership Certificate. The Petitioner and the Regional Government did not encounter any obstacles in implementing the Registration of Ownership Land as a result of the Exchange with Village Treasury Land through the PTSL Program until the issuance of the Certificate of Ownership in Cilacap Regency. Meanwhile, the obstacle faced by the Cilacap Regency Land Office is that the distance between the exchange process and land registration is very long, namely 18 years, which creates obstacles.